Hypertension across the lifespan: Pediatrics. Issue 2 (March 2021) - Esquibel, Karen A.; Moore, Amy; Hilliard, Tara C.; Bruce, Kellie; Mello, Inola
Abstract : How can nurses facilitate cardiovascular care for our young patient population? Abstract : How can nurses facilitate cardiovascular care for our young patient population?